2022
DOI: 10.3389/fnut.2022.935711
|View full text |Cite
|
Sign up to set email alerts
|

Host–microbial co-metabolites modulated by human milk oligosaccharides relate to reduced risk of respiratory tract infections

Abstract: Human milk oligosaccharides (HMOs) are structurally diverse oligosaccharides present in breast milk, supporting the development of the gut microbiota and immune system. Previously, 2-HMO (2'fucosyllactose, lacto-N-neotetraose) compared to control formula feeding was associated with reduced risk of lower respiratory tract infections (LRTIs), in part linked to lower acetate and higher bifidobacteria proportions. Here, our objective was to gain further insight into additional molecular pathways linking the 2-HMO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Bifidobacteria are among the first colonizers of the infant gut and sustaining this abundance of Bifidobacteria is crucial to preserving the gut microbiota composition. Several studies have shown that HMOs influence the gut microbiota composition via bifidogenic and anti-pathogenic effects and by potentially interacting with the gut epithelium to alter the physical interactions between microbes and their hosts 66 . Breastfeeding, due to the supply of HMOs into the gut, promotes the growth of specific HMO-utilizing Bifidobacterium species which are nearly accounting for 50–90% of the total bacterial population found in the feces of breastfed newborns 67 .…”
Section: Hmos and Anthropometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Bifidobacteria are among the first colonizers of the infant gut and sustaining this abundance of Bifidobacteria is crucial to preserving the gut microbiota composition. Several studies have shown that HMOs influence the gut microbiota composition via bifidogenic and anti-pathogenic effects and by potentially interacting with the gut epithelium to alter the physical interactions between microbes and their hosts 66 . Breastfeeding, due to the supply of HMOs into the gut, promotes the growth of specific HMO-utilizing Bifidobacterium species which are nearly accounting for 50–90% of the total bacterial population found in the feces of breastfed newborns 67 .…”
Section: Hmos and Anthropometrymentioning
confidence: 99%
“…Bifidobacteria abundance and metabolic activity could be associated to decreased respiratory tract infections 66 , 72 , 163 . Increased gamma-glutamylation and N-acetylation of amino acids, and decreased inflammatory signaling lipids, are the three most notable molecular pathways 66 .…”
Section: Hmos and Anthropometrymentioning
confidence: 99%
“…infantis and increased levels of bifidobacteria-derived acetic acid were factors contributing to the protective effect of 2 -FL and LNnT against LRTI in infancy [15]. Additional metabolic pathways have been identified, including gamma-glutamylation and acetylation of amino acids, altered by the HMO formula feeding [16]. In our study, the microbial ecosystem of the EHF-fed infants with CMPA likely differed from that of healthy infants.…”
Section: Discussionmentioning
confidence: 71%
“…Martin et al described molecular changes related to HMO feeding and protection from LRTI, including an increase in gamma glutamylation and N-acetylation of amino acids, as well as a decrease in inflammatory lipids. Changes in amino acid and lipid metabolism were linked to Bifidobacterium and Bacteroides species, respectively [16].…”
Section: Introductionmentioning
confidence: 99%
“…O'Mahony referenced a recent study in which HMOs fed to infants gave rise to an "enormous change in metabolism," including increased levels of sphingolipids, important for the development of intestinal invariant natural killer T cells, reduced levels of the T regulatory inhibitor 12,13-dihydroxylated fatty acid, and changes in the gamma-glutamylation of AAs associated with reduction in inflammatory cytokines. 11 The most well-described bacteria-derived metabolites with immunomodulatory activity in the gut are the short-chain fatty acids (SCFA), which comprise acetate, propionate, and butyrate. "SCFAs are really important early in life," explained O'Mahony.…”
Section: Meeting Summarymentioning
confidence: 99%